Constructions of women’s economic empowerment through microfinance in development discourse : a case study of World Vision’s Women’s Self Help Group programme in Eswatini - Nilsen, Alf Gunvald (University of Pretoria, 2023)
Mini Dissertation (MSocSci (Gender Studies))--University of Pretoria, 2022.